THE ROLE OF PRECARPATHIAN NATIONAL UNIVERSITY AS A REFORM THINK TANK IN THE INSTITUTIONAL DEVELOPMENT CAPACITY STRENGTHENING OF TERRITORIAL COMMUNITIES OF THE REGION - Kropelnytska, S.O. (The actual problems of regional economy development, 2018)
The article is investigated the role of a state institution of higher education in shaping and raising the level of institutional capacity of community development in the region. The research is based on the initial results of the real experience of Vasyl Stefanyk Precarpathian National University on the formation of institutional support for the development of the Ivano-Frankivsk region. The structure of institutional development support, which was formed at the university, and non-state institutional provision of the region are revealed. The main aspects of the activity of the “Agents of Change” Project and Educational Center of the Precarpathian University and its role in increasing the institutional capacity of the regional communities' development in the field of project management are outlined. It is concluded that universities play an important role in regional development as think-tanks of reforms and are institutions for the development of territorial communities of the region in co-operation with other structures in the system of its institutional support.